The Refinement on Character education to Strengthening Islamic Education in Industrial Era 4.0 - priyanto, Adun (Nadwa: Jurnal Pendidikan Islam, 2020)
The research is to know the strengthening of Islamic educations in accordance with the need for the Industrial era 4.0 industrial era (turbulence era). Within those advancements, character education has become an oasis in the middle of morality decadences of millennial generation in the present society and a fort to prevent the destruction of a nation. The research method uses literature study by collecting data from documentation using the descriptive-analysis method. The results of the study concluded, Islamic education transformation is greatly required to gain solutions by strengthening Islamic educational management, Islamic educational leadership, and educational policy on character educations. Character education in Islamic Education does not only teach right or wrong but also teaches students to commit to doing the right thing. The character emphasizes practice in the students’ daily lives such as the implementation of, honest (Siddiq), trustworthy (Amanah), smart (fathonah) and conveys the truth (tabligh), in relationship, a good citizen attitude.   AbstrakMasyarakat Islam harus melakukan modernisasi pendidikan Islam dalam segala aspek pendidikan, kurikulum, tata kelola institusi, model dan strategi pembelajaran sesuai dengan kebutuhan era industri 4.0 (era turbulensi). Dalam kemajuan tersebut, pendidikan karakter telah menjadi oase di tengah dekadensi moralitas generasi milenial di masyarakat saat ini dan benteng pencegah kehancuran suatu bangsa. Metode penelitian menggunakan studi pustaka dengan mengumpulkan data dari dokumentasi menggunakan metode analisis deskriptif. Hasil penelitian menyimpulkan, transformasi pendidikan Islam sangat diperlukan untuk mendapatkan solusi dengan memperkuat manajemen pendidikan Islam, kepemimpinan pendidikan Islam, dan kebijakan pendidikan pada pendidikan karakter. Pendidikan karakter dalam Pendidikan Islam tidak mengajarkan benar atau salah, tetapi juga mengajarkan siswa untuk berkomitmen melakukan hal yang benar. Karakter tersebut menekankan pada praktik dalam kehidupan sehari-hari siswa seperti pelaksanaan, jujur (siddiq), amanah (amanah), cerdas (fathonah) dan menyampaikan kebenaran (tabligh), dalam menjalin hubungan, sikap warga negara yang baik.